Human Body as a Legal Phenomenon - Stovba, O.V. (Право и государство №3 (104), 2024)
The paper is dedicated to the reflection on the body as a legal phenomenon. Despite the fact that the body is ontologically closest to us, from a legal point of view, it remains one of the most enigmatic phenomena. Classical jurisprudence traditionally divides all legal entities into subjects of law (the state, individuals, legal entities, the people) and objects of legal relations (property, physical evidence, disputed items, etc.). However, the body cannot be identified within such coordinates. On the one hand, the body itself is not a subject of law. After all, purely incorporeal, abstract entities, such as legal entities or the state, are subjects of law, sometimes without any material embodiment. On the other hand, purely corporeal existence does not yet guarantee legal capacity, as, for example, the presence of a dead body does not necessarily indicate its absence. This situation is fully reflected in the national legislation of Ukraine. Its analysis shows that the human body is not defined as an independent object of legal regulation, and the corresponding legal regime is absent. The most symptomatic manifestation of the total disregard for the legal issues surrounding the body is the absence of a corresponding term even in special medical legislation that regulates organ transplantation, health protection, and medical care. Thus, the phenomenon of the body has now fallen outside the focus of Ukrainian legal scholars. This leads to the absence of a conceptual understanding of the body as a legal phenomenon and uncertainty regarding its legal regulation as such. As a result, it can be stated that the phenomenon of the body should be understood from a philosophical and legal perspective. The result of such reflection is the identification of the following ontological features of the body as a legal phenomenon: syncretism, liminality, and intentionality. This, in turn, provides grounds to assert that normativity is inherently inherent to the body, where the body itself is a hypothesis and a disposition for surrounding individuals, and the inability to communicate with it becomes a sanction. In conclusion, the author argues that the inviolability of the body should be enshrined at the legislative level, making corresponding amendments to the Civil and Criminal Codes of Ukraine.
Keywords: law, body, syncretism, liminality, intentionality